A review on pathogenicity of Aeromonas hydrophila and their mitigation through medicinal herbs in aquaculture. Issue 3 (March 2023) - Semwal, Anurag; Kumar, Avdhesh; Kumar, Neelesh
Abstract: Aeromonas hydrophila is a freshwater, facultatively anaerobic, chemo-organoheterotrophic bacterium that distressed fishes with gastroenteritis, septicemia and causes a disease known as Motile Aeromonas Septicemia (MAS), which affects the aquatic environment. Haemolysin, aerolysin, cytosine, gelatinase, enterotoxin and antimicrobial peptides have been identified as virulence factors in A. hydrophila . Medicinal herbs/plants and their uses are the instant, easily available, cost-effective, efficient and eco-friendly approach for socio-economic, sustainable development of modern aquaculture practice. Phytotherapy either through a dip or by incorporation into the diets is an alternative approach to synthetic pharmaceuticals to diminish the pathogenicity of aquatic environmental pathogens. Due to the presence of remarkable phytoconstituents like flavonoids, alkaloids, pigments, terpenoids, steroids and essential oils, the medicinal plant exhibits anti-microbial, appetite-stimulating, anti-stress, growth-promoting and immunostimulatory activities. Aqua-industry preferred phytotherapy-based techniques/compounds to develop resistance against a variety of aquatic pathogens in culturable fishes because they are inexpensive and environment-friendly. As a result, this review elaborates on the diverse applications of phytotherapy as a promising tool for disease management in aquaculture and a major step toward organic aquaculture. Highlights: Aeromonas spp. causes significant economic losses to aquaculture. Medicinal plants are biocompatible and cost-efficient. Potent bioactive compounds of medicinal plants exhibit antimicrobial activities. Phytotherapy represents a promising tool for the sustainability of the aquaculture.